Особливості сучасного розвитку Wi-Fi мереж - Пантелеев, В. О.; Ажраб Басіл Саліба; Нуіна Маруане (ХНУРЕ, 2020)
The object of the study is the convergent 4G communication network and the modern technology of wireless access to the Internet - Wi-Fi. The subject of the research is the methods of security of elements and mechanisms of information protection in converged 4G and Wi-Fi networks. The purpose of the work is to study the technologies and problems of the protection of modern wireless access technology and the convergent network of general use. Research methods - the analysis of the prospects for the development of Wi-Fi and 4G and features of modern development has been carried out.